Menumbuhkan Jiwa Kewirausahaan Santri di Ma’had al-Ittihad al-Islami Camplong Sampang - Fahrurrozi; Karman (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2022)
This study aims to find out the strategy of Pesantren Mahad Al-Ittihad Al-Islami Camplong in fostering the entrepreneurial spirit of santri and to know the impact of the strategy of pesantren Mahad Al-Ittihad Al-Islami Camplong in fostering the entrepreneurial spirit of santri. This research uses qualitative approach with deriftive type. The technique of checking the validity of the data through the persistence of researchers, and triangulation. The results of this study showed that the strategy carried out by Ma'had al-Ittihad al-Islami Camplong by means of entrepreneurial-based education planning. The purpose of an entrepreneurial education is to instill the values of the entrepreneurial spirit to the students because the process of an educational planner will provide clarity of direction that is certain and can be implemented more effectively and efficiently. Coaching and training, coaching and training is a process that will educate students to have readiness in the business world and can create a communication network, with the right training will also support students to know how to entrepreneurship correctly and more precisely. Specifically, there are six impacts of the strategy that has been implemented by ma'had al-Ittihad al-Islami Camplong, namely confidence, self-reliance, courage, leadership, honesty, and discipline.